Morfogênese de gramíneas nativas sob níveis de adubação nitrogenada - Machado, Juliana Medianeira (2010)
In the period May 2008 to March 2009 experiment was conducted in an area of the Federal University of Santa Maria, in order to evaluate the characteristics and structural traits of eight native grasses (Andropogon lateralis, Aristida laevis, Axonopus affinis, Erianthus angustifolius, Paspalum notatum, Paspalum plicatulum, Piptochaetium montevidense and Sorghastrum pellitum) under nitrogen levels (zero and 100 kg /ha of nitrogen). The experimental design was of blocks randomized with three replications in factorial arrangement of 8 x 2 (native grasses x nitrogen). Accumulated thermal time of 350 and 700 degree days determined the interval between cuts to the species of prostrate growth habit and caespitose, respectively. The highest rates of elongation were observed in Aristida laevis, Erianthus angustifolius, Paspalum plicatulum and Sorghastrum pellitum when received nitrogen. For leaf appearance rate, phyllochron, leaf senescence rate, duration of elongation, the lifespan of the leaves, number of green leaves and leaf length difference was found between species.